The SketchUp workflow for architecture - Brightman, Michael (Wiley, 2013)
Includes index; This book is for architects and related design professionals who want to take their SketchUp use to the next level. In-Depth tips and techniques show users how to use SketchUp and its related suite of tools in every stage of the design process -- Provided by publisher